Osteoporosis and cardiovascular disease: an update. (3rd August 2015) - Lello, S.; Capozzi, A.; Scambia, G.
Abstract: Osteoporosis (OP) and cardiovascular diseases (CVD) are the most important causes of mortality and morbility in the elderly. Lots of studies showed a correlation between bone loss and cardiovascular risk mediated by the vascular calcification. The relationship between OP and CVD could be firstly explained by their common risk factors such as age, smoking, alcohol consumption, physical activity and menopause. However, other different hypotheses were proposed to clarify this link. Multiple factors, for example bone morphogenetic proteins, osteoprotegerin, receptor activator of nuclear factor κB ligand, parathyroid hormone, phosphate, oxidized lipids and vitamins D and K seemed to be involved in both conditions, indicating a possible common pathophysiologic mechanism. We review and discuss the available data describing this association. Further studies are necessary to better investigate similarities between OP and CVD. Chinese abstract: 骨质疏松症和心血管疾病是老年人最重要的死亡和发病原因。大量研究证明了骨质流失和由血管钙化导致的心血管疾病之间的相关性。骨质疏松和心血管疾病之间的联系首先能用它们共同的危险因素如年龄、吸烟、饮酒、体力活动和绝经来解释。然而，其他不同的假设澄清了这种联系。许多因子如骨形成蛋白、骨保护蛋白、核转录因子受体激动剂kB配体、甲状旁腺素、碳酸盐、氧化脂质及维生素D和K似乎也与两者有关，暗示可能有共同的病理生理机制。本文回顾性分析了现有的描述两者关系的资料。为更好的了解骨质疏松症和心血管疾病间的相似之处需要进一步的研究。